Pathogenic and non-pathogenic Agrobacterium tumefaciens, A-rhizogenes and A-vitis strains form biofilms on abiotic as well as on root surfaces - Abarca-Grau, Ana M.; Penyalver, Ramón; López, María M.; Marco-Noales, Ester (2017)
Pathogenic and non-pathogenic Agrobacterium tumefaciens, A. rhizogenes and A. vitis strains growing in minimal liquid medium adhered to different abiotic surfaces, forming biofilms at initial stages of development. Agrobacterium tumefaciens and A. vitis strains were able to attach to both polystyrene and polypropylene materials, whereas the A. rhizogenes strains only bound to polystyrene surfaces. Strains of the three species were also able to form biofilms on borosilicate coverslips. It is concluded that their ability to adhere to and form nascent biofilms on abiotic surfaces is dependent on the Agrobacterium species (biovar), surface material and growth conditions. Furthermore, tumorigenic A. tumefaciens and A. vitis strains, and the biological control agent A. rhizogenes strain K84, bound tightly to and formed complex biofilms on the surface of tomato root tips ex planta. More importantly, in planta assays confirmed that all three Agrobacterium spp. strains efficiently colonized tomato seedlings and also formed biofilms on roots. These complex structures, as revealed by scanning electron microscopy, were composed of numerous bacterial cells arranged in different ways: either dense and continuous carpets, large aggregates embedded in extra-cellular material or globular mushrooms traversed internally by channels. Confocal laser scanning microscopy, using GFP-marked derivative strains, corroborated the presence of live, three-dimensional and thick green fluorescent structures attached to plant material. This study illustrates that besides A. tumefaciens, strains of the species A. rhizogenes and A. vitis are also able to build biofilms on abiotic as well as on root surfaces.